Let’s solve the problem step by step.
Part A
-
Finding the GCF (Greatest Common Factor): The expression is \( 2x^2 + 22x + 60 \). We can find the GCF of the coefficients (2, 22, and 60). The GCF is \( 2 \).
-
Factoring out the GCF: Factoring out \( 2 \): \[ 2(x^2 + 11x + 30) \]
So, the quadratic with the GCF factored out is \( 2(x^2 + 11x + 30) \).
-
Identifying a, b, and c: In the expression \( x^2 + 11x + 30 \):
- \( a = 1 \)
- \( b = 11 \)
- \( c = 30 \)
Filling in Part A:
- The GCF is = 2
- The quadratic with the factored out the GCF is x² + 11x + 30
- \( a = 1 \)
- \( b = 11 \)
- \( c = 30 \)
Part B
Using the quadratic formula \( x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \):
- Calculate the discriminant: \[ b^2 - 4ac = 11^2 - 4(1)(30) = 121 - 120 = 1 \]
- Now apply the quadratic formula: \[ x = \frac{{-11 \pm \sqrt{1}}}{2(1)} = \frac{{-11 \pm 1}}{2} \]
Filling in Part B:
- \( x = \frac{{-11 \pm 1}}{2} \)
Part C
Now we need to solve for x using the results from Part B.
- Calculating the two potential values for \( x \):
- For the positive case: \[ x = \frac{{-11 + 1}}{2} = \frac{{-10}}{2} = -5 \]
- For the negative case: \[ x = \frac{{-11 - 1}}{2} = \frac{{-12}}{2} = -6 \]
Filling in Part C:
- \( x = -6 \) lesser number
- \( x = -5 \) greater number
Final Summary:
-
Part A:
- The GCF is = 2
- The quadratic with the factored out the GCF is x² + 11x + 30
- \( a = 1 \)
- \( b = 11 \)
- \( c = 30 \)
-
Part B:
- \( x = \frac{{-11 \pm 1}}{2} \)
-
Part C:
- \( x = -6 \) lesser number
- \( x = -5 \) greater number